Pengaruh Self Efficacy, Artificial Intelligence dan Disiplin Kerja Terhadap Kinerja Karyawan dengan Motivasi Sebagai Variabel Intervening di PT. Adira Dinamika Multifinance Kota Padang - Akbar .; Vicky Brama Kumbara; Chintya Ones Charli (CV. ITTC INDONESIA, 2026)
This study aims to determine the extent of the influence of Self-Efficacy, AI Implementation, and Work Discipline on Employee Performance with Motivation as an intervening variable at PT Adira Dinamika MultiFinance Padang. The research utilized a documentation method and primary data. The results obtained based on the partial test (t-test) indicate that: Self-Efficacy has a significant effect on Motivation at PT Adira Dinamika MultiFinance Padang; AI Implementation does not have a significant effect on Motivation at PT Adira Dinamika MultiFinance Padang; Work Discipline has a significant effect on Motivation at PT Adira Dinamika MultiFinance Padang; Self-Efficacy has a significant effect on Employee Performance at PT Adira Dinamika MultiFinance Padang; AI Implementation does not have a significant effect on Employee Performance at PT Adira Dinamika MultiFinance Padang; Work Discipline has a significant effect on Employee Performance at PT Adira Dinamika MultiFinance Padang; Work Motivation has a significant effect on Employee Performance at PT Adira Dinamika MultiFinance Padang; Self-Efficacy has a significant effect on Employee Performance through Work Motivation as an intervening variable at PT Adira Dinamika MultiFinance Padang; AI Implementation does not have a significant effect on Employee Performance through Work Motivation as an intervening variable at PT Adira Dinamika MultiFinance Padang; and Work Discipline has a significant effect on Employee Performance through Work Motivation as an intervening variable at PT Adira Dinamika MultiFinance Padang..